(3bGWYI GddLGL aj JMbjb Md GdNQGLs - (3GdcQcj GdYGedj, CHh GdMSf, GdeMbb GdKGfj, GdeMbb GdKGfj, Ydj Hf GdMSjf Hf YHO GdYGdj GdcQcj GdYGedj, J (B940(3g` (B1534(3es ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj CjO cdeI GdMb HGdHQGgjf GdbGWYI (B... (3hQJHJgG Ydi KdGK ebOeGJ hNeS ebGdGJ hNGJeI (B... (3GdebOeI GdChdi aj CbSGe GdCQVjf hgj aj GdUd Ydi bSejfs
(3BNQgG (B:s
(3BNQgG(B: (3heG RdfG fSeY aj cKjQ eef YGUQfGge dG SjeG TjNfG GdCYXe Ydj Hf gdGd hZGdH Xfj Cfg HZjQ hGSWI Hd HGdeTGagI Cfg dG jLhR def YdjN GdNQGL hGdebGSeI SQbJg (B... (3hGddg GYde HMbGFb GdCehQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L(B4: 281s
(3GdPQjYI, L (B17: 7s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis